Predictors of online health information seeking behavior: Changes between 2002 and 2012 - Li, Jinhui (2016)
The Internet has become an important and preferred source of health information. Although the literature has highlighted several key predictors that influence an individual’s online health information seeking behavior, insufficient attention has been paid to the changes in the predictors’ roles and effects over time. This study explores and compares the effects that specific predictors had on online health information seeking behavior over a period of 10 years by integrating and analyzing two Pew datasets collected in 2002 and 2012. Hierarchical regression analyses indicate that socio-demographic factors and overall health condition are significant predictors that had an increasing impact on online health information seeking behavior. However, the impact of Internet usage decreased significantly from 2002 to 2012. A comparison across time contributes to a vertical understanding of the changes in online health information seeking behavior and its predictors and helps health professionals and researchers tailor their informational interventions to meet the up-to-date needs and preferences of users.